2018
DOI: 10.1007/s12094-018-1846-z
|View full text |Cite
|
Sign up to set email alerts
|

Integral nutritional approach to the care of cancer patients: results from a Delphi panel

Abstract: There is an important variability in the management of cancer patient nutrition, which is associated with the absence of a national consensus on nutritional support in this field. Given the incidence of nutritional disorders in cancer patients, a specialist in clinical nutrition (regardless of his/her specialty) should be integrated into the strategic cancer plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
19
0
4
Order By: Relevance
“…This may be partly attributed to the lack of uniformity in the cut-off used to define sarcopenia on computed tomography (CT) images; this would directly influence the statistical results. Selection bias caused by the difference in patients' clinical stage is also likely to affect the results [18,19]. Therefore, we evaluated the sarcopenic status in the Japanese population using cut-off values established and used specifically in this ethnic population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be partly attributed to the lack of uniformity in the cut-off used to define sarcopenia on computed tomography (CT) images; this would directly influence the statistical results. Selection bias caused by the difference in patients' clinical stage is also likely to affect the results [18,19]. Therefore, we evaluated the sarcopenic status in the Japanese population using cut-off values established and used specifically in this ethnic population.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary counseling and nutritional support have also been reported to positively influence morbidity outcomes and QOL in cancer patients undergoing radiation therapy [33]. Early consultation with a skilled nutritionist is widely accepted to be beneficial for cancer patients receiving anticancer treatments [18,19,[34][35][36] and for those in advanced stages of malignancy [37]. Collectively, these findings indicate that clinicians should carefully evaluate patients' nutritional conditions, with particular emphasis on the presence of sarcopenia, and consider nutritional interventions throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is a wide agreement that early consultation with a professional (physician and dietician) with documented skills in clinical nutrition, specifically for oncology patients, is beneficial for cancer patients receiving anticancer treatments [19,21,[25][26][27] as well as for those in the advanced stages of disease [22]. However, there are few clinical studies investigating the effects of nutritional support in cancer patients undergoing CT or radiotherapy (RT).…”
Section: Evidence Supporting Nutritional Interventionsmentioning
confidence: 99%
“…However, the most alarming aspect reported in the preliminary results of this study is the large number of cancer patients in Spain for whom no nutritional diagnosis is made. In this respect, Duran-Poveda et al conducted a study using the Delphi method, involving 52 medical specialists who treated cancer patients, and found that fewer than 30% of these patients were screened to assess their risk of malnutrition [13].…”
Section: Discussionmentioning
confidence: 99%